Malaria in Assam: A challenge - Pardal Maninder Pal; Bhalwar Rajvir; Mehta Vijay; Mahendraker Ajay; Mehta Ashwini (Wolters Kluwer Medknow Publications, 2009)
Research Question: What is the trend of malaria and proportion of Plasmodium falciparum infections amongst troops of the Army units deployed in Assam over the last 5 years? Study Design: Retrospective cross -sectional descriptive study. Setting: Army units deployed in the state of Assam over the last 5 years. Participants: Population of army units deployed in the state of Assam over the last 5 years. Statistical Analysis: Percentage, Chi square. Results: Malaria contributed to 3.60% to 7% of all hospital admissions over the period of 5 years. The overall malaria incidence showed a significantly increasing trend during the study period. (Chi square for linear trend = 5.19; P = 0.023). Out of these, P falciparum contributed 86% to 98%. The proportion of P falciparum infections showed a significantly increasing trend from 2005 to 2006. (Yate′s corrected Chi square = 7.123; P = 0.008).